(untitled) (Journal of Material Science and Technology Research, 2025)
Magnetoelectric (ME) effects in ferromagnetic-piezoelectric heterostructures manifest themselves as a change in the polarization of the structure in an external magnetic field or a change in magnetization in an electric field. The effects are used to create magnetic field sensors, tunable electronic devices, and n1 ew data processing elements. To ensure the thermal stability of these devices, it is important to understand the temperature dependence of the ME effect characteristics. In this paper, we investigated the direct resonant ME effect in a monolithic heterostructure consisting of a langatate single crystal with FeBSiC amorphous ferromagnet films deposited on its surface. It was shown that heating of the structure from 220 K to 340 K resulted in a decrease in the quality factor of the acoustic resonance followed by a decrease in the ME coefficient. Annealing the structure in the presence of magnetic field led to an enhancement in the ME coefficient, a decrease in the optimal bias field, and improvement in thermal stability of the ME effect.